Analisis Kontribusi Keuntungan Atas Produk- Produk Pada CV. Salim Tailor Di Tenggarong (Penerapan Linear Programming Metode Simplek) - Lisa Novita Sari; Yonathan Palinggi; Raudatul Adawiyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The main objective of this study was to find out whether the production amount of CV. Salim Tailor In Tenggarong has been at the optimum point to generate maximum profit contribution and to know which type of products that generate maximum profit contribution from various products produced by CV Salim Tailor in Tenggarong.The research result is indicated that business well get maximal profit from product Pants (X1) with respective optimal production quantities are rounded to 24,4253 unit it’s mean that 24 unit plus 1 unit product on process productions 42,53% and also product PDL (X5) with respective optimal production quantities are rounded to 13,472% unit it’s mean that 13 unit plus 1 unit product on process productions 4,72% with the maximum profit Rp. 29.188.950 for 1 month.For the time of measurement and cutting or process 1 (S1) still leave time during 5,0833 minute, this is indicated that the company have a lost time on the process 1 for more or less 0,08 hours for 1 month. Keywords: Profit Contributions (Application of Linear Programming Simplex Method)